Higher education, English, and the idea of 'the West': globalizing and encountering a global south regional university. Issue 5 (3rd September 2018) - Le Ha, Phan
ABSTRACT: This article is about 'global south' actors and global south–global south interactions in the context of the internationalization of higher education (IHE), with a focus on a Vietnamese university and the mobilities of students moving through this educational space. It discusses in what ways this university sees its multi-layered association with the Philippines as a bridge, a catalyst that could fulfill its aspirations for internationalization which is largely attached to English, 'the West', the idea of 'the West', and becoming global. The article shows how the participation in and consumption of such aspirations/desires by new IHE players could reproduce and widen social inequalities between and within 'global south' actors but also bring about (unexpected) possibilities and transformations in a context of considerable educational mediocrity. It points to the contradictions inherent in these developments and the ways in which these developments may feed into uneven access to and experiences of IHE.